Hypoxia promotes the tolerogenic phenotype of plasmacytoid dendritic cells in head and neck squamous cell carcinoma. (28th December 2021) - Fan, Cui; Wu, Jichang; Shen, Yilin; Hu, Haixia; Wang, Quan; Mao, Yufeng; Ye, Bin; Xiang, Mingliang
Abstract: Objective: We aim to review the roles of plasmacytoid dendritic cells (pDCs) in head and neck squamous cell carcinoma (HNSCC) and explore the effects of hypoxia on the tolerogenic transformation of pDCs. Background: pDCs, best known as professional type I interferon‐secreting cells, play key roles in immune surveillance and antitumor immunity. Recently, pDCs have been shown to be tolerogenic and correlate with poor prognosis in a variety of cancers, including HNSCC. However, it remains unclear what drives the tolerogenic transformation of pDCs in the HNSCC microenvironment. Hypoxia, a prominent hallmark of the tumor microenvironment (TME) of HNSCC, can interfere with multiple immune cells and establish an immunosuppressive TME. Methods: In this review, we summarize the antitumor and protumor functions of pDCs, explore the effects of hypoxia on the migration and maturation of pDCs, and discuss related mechanisms in HNSCC. Conclusions: pDCs mainly display protumor functions in HNSCC. The hypoxic TME in HNSCC can enhance the migration of pDCs and inhibit the differentiation and maturation of pDCs, promoting the tolerogenic phenotype of pDCs. Abstract : HNSCC is a type of immunogenic tumor characterized by the immunosuppressive tumor microenvironment. We review the antitumor and protumor functions of pDCs in HNSCC, discuss the effects of hypoxia on tumor‐infiltrating pDCs in HNSCC and recommend that hypoxia and related metabolites, such as lactate and adenosine, could damage the IFN‐α secretion and antigen presentation of pDCs, and enhance the migration and Treg induction of pDCs in HNSCC.